Programma: 19-22 september Crystal Theatre; 26-29 september Doctor Doome's Living Waxworks; 3-6 oktober White Dreams; 10-13 oktober Katheater - Flaum, Mick,
Programma: 19-22 september Crystal Theatre; 26-29 september Doctor Doome's Living Waxworks; 3-6 oktober White Dreams; 10-13 oktober Katheater.